Plant communities in Shivapuri Nagarjun National Park, Central Nepal - Dhakal, Tilmaya; Thapa, Lal Bahadur; Pokhrel, Chandra Prasad; Yadav, Ram Kailash Prasad (Banko Janakari, 2023)
This study analyzes the plant communities in the Shivapuri Nagarjun National Park (SNPP), Nepal. A survey was done in the National Park in 2020 using quadrat sampling. The study sites were characterized by specific plant communities Four different sites, Sundarijal (SJ), Panimuhan (PA), Okhreni (OK), and Bagdwar (BD) were identified for the sampling based on elevation and aspects. The density, frequency, IVI, basal area, DBH, and diversity indices of plant species were measured. A total of 32 tree species representing 30 genera and 19 families were identified. Quercus semecarpifolia, Lindera nacusua, Castanopsis tribuloides, and Schima wallichii showed the highest density and IVI in BD, OK, SJ, and PA, sites, respectively. Q. semecarpifolia and, Pyrus pashia, S. wallichii and C. tribuloides were the most frequent species in BD, OK, SJ, and PA, sites, respectively. Similarly, the species Q. semecarpifolia, Pinus roxburghii, C. tribuloides and S. wallichii were the species having the highest basal area in the BD, OK, SJ, and PA sites, respectively. The BD site harbors numerous trees with DBH exceeding 50 cm, whereas the SJ site boasts a significant abundance of trees with DBH below 25 cm. The effect of the tree canopy, litter, and shrub cover, grazing, and cutting on species composition was found significant. Simpson’s diversity index ranged from 0.72 - 0.88, and the Shannon-Weiner index from 1.79- 2.49. Similarly, Pielou’s evenness was 0.32 - 0.47.